Modification of corncob-derived cellulose using Hexadecyltrimethylammonium Bromide and Propylene Carbonate - Ng Yee Shui; Ooi Zhong Xian; Teoh Yi Peng; Ooi Mei Lee (E3S Web of Conferences)
This study reported the modification of corncob cellulose using propylene carbonate and hexadecyltrimethylammonium bromide (CTAB) to impart the desired functionalities. The modified corncob cellulose was characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and zeta potential. Different parameters were studied in modifying functionalities of corncob cellulose, i.e., the ratio of CTAB and propylene carbonate, retention time and temperature. After modification, an increase in weight percent was obtained. According to the FTIR spectrum, there was an extra peak at 1780 cm-1 which belongs to C=O groups and an increase in intensity at 1000–1300 cm-1 which belongs to CN stretching of the quaternary ammonium group. SEM images and zeta potential results supported the quaternary ammonium group was successfully grafted on isolated corn cob cellulose, which are essential for initiating photocatalytic reactions.